2-Deoxyglucose and Beta-Hydroxybutyrate: Metabolic Agents for Seizure Control - Rho, Jong M.; Shao, Li-Rong; Stafstrom, Carl E. (Frontiers in Cellular Neuroscience, 2019)
Current anti-seizure drugs (ASDs) are believed to reduce neuronal excitability through modulation of ion channels and transporters that regulate excitability at the synaptic level. While most patients with epilepsy respond to ASDs, many remain refractory to medical treatment but respond favorably to a high-fat, low-carbohydrate metabolism-based therapy known as the ketogenic diet (KD). The clinical effectiveness of the KD has increasingly underscored the thesis that metabolic factors also play a crucial role in the dampening neuronal hyperexcitability that is a hallmark feature of epilepsy. This notion is further amplified by the clinical utility of other related metabolism-based diets such as the modified Atkins diet and the low-glycemic index treatment (LGIT). Traditional high-fat diets are characterized by enhanced fatty acid oxidation (which produces ketone bodies such as beta-hydroxybutyrate) and a reduction in glycolytic flux, whereas the LGIT is predicated mainly on the latter observation of reduced blood glucose levels. As dietary implementation is not without challenges regarding clinical administration and patient compliance, there is an inherent desire and need to determine whether specific metabolic substrates and/or enzymes might afford similar clinical benefits, hence validating the concept of a “diet in a pill”. Here, we discuss the evidence for one glycolytic inhibitor, 2-deoxyglucose (2DG) and one metabolic substrate, β-hydroxybutyrate (BHB) exerting direct effects on neuronal excitability, highlight their mechanistic differences, and provide the strengthening scientific rationale for their individual or possibly combined use in the clinical arena of seizure management.